(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
At the end of World War I, there was an adjustment in the field of science, literature, arts and education, which was supported by the new structure of the new international system. This was the case of the International Institute of Intellectual Cooperation – considered as the former UNESCO. The independence of the Institute of Paris from the League of Nations – of which Mexico had been excluded – enabled the country early participation (1926). From that time until the Institute was informally dissolved, Mexico worked with the institute. The general lack of knowledge of this historical episode, in which also the Mexican Commission of Intellectual Cooperation was created, limits our vision of the support the post-revolutionary government granted to the scientific and intellectual activities during the 1920s and 1930s. The purpose of this paper is to make a first historiographic approach to the subject and provide an overview of the activities carried out by Mexico as part of its collaboration with the International Institute of Intellectual Cooperation.